THE IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION IN MERDEKA CURRICULUM ON TEACHING STRATEGIES AND STUDENTS’ LEARNING MOTIVATION IN ENGLISH CLASSROOM - Miranty, Dini; Sundari, Hanna; Puspitasari, Maya (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2026)
This study investigates the impact of Differentiated Instruction (DI) within the Merdeka Curriculum on teaching strategies and students’ learning motivation in an English classroom at a public senior high school. A qualitative descriptive case study design was employed involving two English teachers and twelve students. Data were collected through classroom observations, interviews, and documentation. The findings indicate that teachers implemented DI through four main dimensions: content, process, product, and learning environment. Various strategies such as group discussions, project-based learning, and interactive activities were applied to accommodate students’ diverse abilities. The implementation of DI enhanced students’ engagement, confidence, and participation in English learning. However, challenges such as limited time, lack of diagnostic assessment skills, and insufficient training affected the consistency of implementation. Overall, DI contributes positively to student-centered learning and increases learning motivation, although further professional development is needed for optimal implementation.